Litigation in Social Legislation : A Study with Iraqis Legislation - Rasheed, Saba (Journal of Legal Sciences, 2023)
The judicial oversight over the administration’s work and the administration’s right to sue its clients is getting stronger in the face of the financial aspects in countries that refuse to continue the socialist-interventionist approach. These countries resort to the new approach of the state neutrality. This calls for an examination of the aspects of legislation that the Ministry of Labor deals with and its right to litigation and procedures prior to benefits. This is in particular the financial ones for those covered by them.